Molecular characterization of resistance mechanisms in Pseudomonas aeruginosa isolates resistant to carbapenems - Mona Shaaban; Ahmed Al-Qahtani; Mohammed Al-Ahdal; Rasha Barwa (Journal of Infection in Developing Countries)
Introduction: Emergence of carbapenem resistance in Pseudomonas aeruginosa increases the therapeutic dilemma. In this study, we investigated various mechanisms involved in the resistance of P. aeruginosa clinical isolates to carbapenems.